Pengaruh Mind Mapping dengan Media Benda Konkret Terhadap Hasil Belajar Siswa - Antyaningrum, Yosi (2016)
Takes place in class IV SD Muhammadiyah 22 Sruni Surakarta is still very simple, strategy and media used, teachers still very simple and not in accordance with the material to be studied so that the student's level of understanding is still lacking thus student learning outcomes is not the maximum. Teachers should use diverse media and strategies to support the learning process. In this research grade teacher tried to implement a strategy with the media mind mapping concrete objects. This research aims to know is there any influence and how much influence the application of Mind Mapping strategies with media objects kokret against the results of student learning on subjects IPA in class IV SD Muhammadiyah 22 Sruni Surakarta years Lessons 2015/2016. This type of research is research experiments. Data analysis using simple regression test (test F), Hypothesis test (test t) and a test of determination (r2). With the t-test analysis results between mind mapping strategy with variable media objects, concrete and result variables studied in class experiments obtained tcount 3.050 and ttabel 2.048. The results of calculation show that tcount 3,050 > ttabel 2.048. On the test F (test regression), obtained an Fcount = 9,303 and Ftabel = 4.17. Fcount 9.303 > Ftabel 4.17. This shows that there is a linear relationship between mind mapping strategy with concrete objects, media (X) and (Y) the learning outcomes. Test on r2 known media mind mapping strategies with concrete objects have an influence of 24% for the enhancement of student learning outcomes. Thus it can be concluded that the strategy of mind mapping with concrete objects, the media has a great influence towards the results of student learning. Keywod: (mind mapping, concrete objects, the results of the study)